Antioxidant Effect of Soymilk Fermented by Lactobacillus plantarum HFY01 on D-Galactose-Induced Premature Aging Mouse Model - Li, Chong; Fan, Yang; Li, Shuang; Zhou, Xianrong; Park, Kun-Young; Zhao, Xin; Liu, Huazhi (Frontiers in Nutrition, 2021)
The aim of this study was to investigate the antioxidant effect of soymilk fermented by Lactobacillus plantarum HFY01 (screened from yak yogurt) on mice with premature aging induced by D-galactose. In vitro antioxidant experiment results showed that compared with unfermented soymilk and Lactobacillus bulgaricus-fermented soymilk, L. plantarum HFY01-fermented soymilk (LP-HFY01-DR) had better ability to scavenge the free radicals 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) diammonium salt (ABTS). Histopathological observation with hematoxylin-eosin, Masson’s trichrome, and toluidine blue staining showed that LP-HFY01-DR could protect the collagen of skin cells, reduce the release of mast cells, inhibit skin injury, improve disordered liver cell arrangement, reduce the infiltration of inflammatory cells, reduce steatosis, reduce congestion of the spleen, reduce damage to spleen corpuscles, and increase lymphocyte levels. Biochemical experiment results showed that LP-HFY01-DR could effectively upregulate glutathione (GSH), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) levels and decrease malondialdehyde (MDA) content in the liver, brain, and serum. Real-time quantitative reverse transcription polymerase chain reaction further showed that LP-HFY01-DR could promote the relative expression levels of the genes encoding for cuprozinc superoxide dismutase (Cu/Zn-SOD, SOD1), manganese superoxide dismutase (Mn-SOD, SOD2), CAT, GSH, and GSH-Px in the liver, spleen, and skin. In addition, high-performance liquid chromatography results revealed daidzin, glycitin, genistin, daidzein, glycitein, and genistein in LP-HFY01-DR. In conclusion, LP-HFY01-DR could improve the antioxidant capacity in mice with premature aging induced by D-galactose.